Plausible changes in wheat‐growing periods and grain yield in China triggered by future climate change under multiple scenarios and periods. (12th November 2021) - Liu, Yujie; Chen, Qiaomin; Chen, Jie; Pan, Tao; Ge, Quansheng
Abstract: Wheat is one of the most common and productive crops in the world, and the growth and production of wheat are sensitive to climate change. Climate change affects wheat phenology by influencing sowing/maturity dates and the duration of growing stages, and ultimately affects the grain yield. Reliable prediction of changes in wheat yield is significant for maintaining global food security. However, studies addressing the potential impact of crop phenology changes on grain yield are rarely reported, which is a big challenge. Using the CERES‐Wheat model and first‐order differential equation models, we quantified the impact of future climate change on wheat phenology and grain yield for two periods (P1: 2011–2040; P2: 2041–2070) under three representative concentration pathways (RCP2.6, RCP4.5, RCP8.5) in China's two main wheat‐growing areas (Northwest Spring Wheat‐Growing Area (NWSWA) and Huang–Huai–Hai Winter Wheat‐Growing Area (HHWWA)); the baseline period was 1981–2010. Accumulated thermal time during the whole growing period (WGP) tends to significantly increase in NWSWA and HHWWA under all RCPs and periods. This rising accumulated thermal time will reduce the time to anthesis and maturity and shorten the vegetative growing period (VGP), reproductive growing period (RGP), and the WGP. In P2, spring wheat grain yield is projected to diminish by a regional average of 2.67% for RCP2.6, 4.07% for RCP4.5, and 5.66% for RCP8.5, which is dominated by the lower accumulated solar radiation during the VGP in NWSWA. Additionally, for the winter wheat grain yield in HHWWA in P2, its grain yield reduction is projected to decline by 4.8% (RCP2.6), 7.9% (RCP4.5), and 9.8% (RCP8.5), which is caused by increasing accumulated thermal time in the VGP. These results suggest that breeding high‐temperature‐tolerant varieties with high calorie requirements is an adaptive strategy to mitigate the negative impact of climate change on wheat yield in the study areas. Abstract : The thermal time tends to increase under future climate scenarios in China. Rising accumulated thermal time is likely to shorten the whole growing periods. Breeding high‐temperature‐tolerant varieties is helpful to climate change adaptation.